Intraoperative hemodynamic optimization using the hypotension prediction index vs. goal-directed hemodynamic therapy during elective major abdominal surgery: the Predict-H multicenter randomized controlled trial - Lorente, Juan V.; Ripollés-Melchor, Javier; Jiménez, Ignacio; Becerra, Alejandra I.; Mojarro, Irene; Fernández-Valdes-Bango, Paula; Fuentes, Maria A.; Moreno, Ana; Agudelo, Maria E.; Villar-Pellit de la Vega, Angel; Ruiz-Escobar, Alicia; Cortés, Azahara; et al. (Frontiers in Anesthesiology, 2023)
Background Intraoperative hypotension (IOH) is associated with increased morbidity and mortality after major abdominal surgery but remains significant even when using goal-directed hemodynamic therapy (GDHT) protocols. The Hypotension Prediction Index (HPI) is a machine learning-derived parameter that predicts arterial hypotension. We tested the hypothesis that an HPI-based protocol reduces the duration and severity of hypotension compared with a GDHT protocol during major abdominal surgery. Methods This is a parallel-arm double-blinded multicenter randomized trial involving adult patients undergoing elective major abdominal surgery at five centers. Patients were optimized according to a previously recommended GDHT protocol (GDHT group) or the HPI value (HPI group). Hemodynamic optimization in both groups started 15 min after the surgical incision. The primary outcome was the intraoperative time-weighted average of mean arterial pressure under 65 mmHg (TWA-MAP < 65 mmHg). Other metrics for IOH and secondary outcomes, including TWA below individual baseline values of intraoperative tissue oxygenation (StO2), postoperative AKIRisk, postoperative complications, length of stay, and 30-day mortality, were explored. Results Eighty patients were randomized (40 patients in each group). TWA-MAP < 65 mmHg was 0.06 (25th–75th interquartile range: 0–0.27) mmHg in the GDTH group vs. 0 (0–0.04) mmHg in the HPI group (p = 0.015). Total time with MAP < 65 mmHg per patient was 4.6 (0–21) min in the GDHT group and 0 (0–3) min in the HPI group (p = 0.008). The TWA below the baseline StO2 was 0.40% (0.12%–2.41%) in the GDHT group and 0.95% (0.15%–3.20%) in the HPI group (p = 0.353). The AKIRisk values obtained in the GDHT group were 0.30 (0.14–0.53) and 0.34 (0.15–0.67) in the GDHT and HPI groups (p = 0.731), respectively. Both groups had similar postoperative complications, length of stay, and 30-day mortality. Conclusions An HPI-based protocol reduced intraoperative hypotension compared with a standard GDHT protocol, with no differences in tissue oxygenation and postoperative AKIRisk.